ВИЩА ОСВІТА УКРАЇНИ І БОЛОНСЬКИЙ ПРОЦЕС (Педагогіка вищої та середньої школи, 2007)
In article the question of occurrence of Ukraine in Bolon’s process, the substantive provisions showed to countries-participants of Boloris process, and also some problems accompanying this process is considered.